2020
DOI: 10.3390/ijerph17072311
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Influencing Factors of Biogas Technology Adoption Intention in Pakistan: The Moderating Role of Social Media

Abstract: Environmental degradation and rapid climate change have forced researchers and practitioners to find sustainable practices to save the world. Increasing energy demand is not only consuming scarce natural resources, but also damaging the climate and overall ecosystem. In this regard, biogas technology is beneficial in two ways—by meeting the energy demand and saving natural resources. Pakistan is an agricultural country and has a high potential for producing energy through biogas technology. Therefore, this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 89 publications
4
35
0
Order By: Relevance
“…Therefore, an opportunity exists to explore the effects of industrial life cycle on the economic indicators of the country. Finally, some researchers, such as Hair et al [61], Akbar et al [62], Wang et al [63], and Ali et al [64] suggested an emerging statistical technique, partial least squares structural equation modelling (PLS-SEM) to be applied on different types of datasets in order to obtain interesting findings. Thus, it would be fascinating to apply PLS-SEM in the literature on FLC to bring about some new insights.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an opportunity exists to explore the effects of industrial life cycle on the economic indicators of the country. Finally, some researchers, such as Hair et al [61], Akbar et al [62], Wang et al [63], and Ali et al [64] suggested an emerging statistical technique, partial least squares structural equation modelling (PLS-SEM) to be applied on different types of datasets in order to obtain interesting findings. Thus, it would be fascinating to apply PLS-SEM in the literature on FLC to bring about some new insights.…”
Section: Discussionmentioning
confidence: 99%
“…Fossil fuels (coal, oil, and gas) are the major energy sources of Pakistan [25]. The country spends USD 7 M annually on importing such costly energy sources [26]. According to the Pakistan Economic Survey, households are one of the largest energy consumers in Pakistan, with a share of 49.1% [27].…”
Section: Introductionmentioning
confidence: 99%
“…SNSs reach a large number of people, attract user attention toward environmental problems, raise awareness, and provide information about the adverse impacts of climate change on civil society [ 7 , 8 ]. SNSs can significantly influence individual and collective ecological concerns, environmental attitudes, and users’ pro-environmental behaviors [ 9 , 10 ]. Pro-environmental behaviors refer to the purposeful actions at the individual or community level that benefit the environment or at least decrease the negative effects on the environment [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%